A semi-automatic competition analysis tool for swimming - Balius, X.; Ferrer, V.; Roig, A. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: On the occasion of the Xth FINA World Championships held in Barcelona in 2003, the Olympic Training Center (CAR) developed a new semi-automatic tool to analyse the mean velocities, mean frequencies and mean stroke lengths of the swimmers. All semi-finals and finals of the swimming competition were recorded and analysed. Calculated results were published the same afternoon of the competition on a specially designed web site for consultation. Swimmers, coaches, press and general public were the target users of the information shared by the research team. Four video cameras recorded the swimming pool sending their signal to four analogue-to-digital video cards. The signal was post-processed with an specially designed software that automatically located the pass of the swimmers head through specific spaces of the recorded image. The objectives of the project were: To develop a tool to speed up the data gathering of the competition analysis; To design a form to personalise and ease the understanding of results for its use during competition and; To improve the process required before publishing the results on the net for swimmers, coaches, press and general public. Methods The video recording (25 Hz) of the swimming pool was done with 4 analogue cameras (JAI Corporation CV-S3300). The cameras were placed vertically to the pool recording 4 different transversal spaces. The SwissTiming competition race start signal was automatically registered to synchronise the video. 4 PCs Pentium 4, 2GHz, 256Mb RAM, 40Gb HD were used to process data and to format the results with a specially designed software. Results / Discussion Results published on a specially made web site (http://www.minorisa.org/fes/dades/finabcn03/) consisted of a 9- page report. A first general page and eight personalised for every swimmer. Specially made reports for all races where developed to ease the understanding of the given data. All objectives were accomplished taking into account that the tool seemed to work properly and on a good time basis after the end of the last race of every afternoon`s competition. The accomplishement to personalise all information, respecting a specially designed base, seemed to ease the understanding by coaches, swimmers and media.